Effects of Moringa (Moringa oleifera L.) Leaf Liquid Organic Fertilizer and NPK Dose on Cauliflower Growth and Curd Yield in Tomohon, Indonesia. - Tulung, Stella Maria Theresia; Supit, Paula Clara Heinny; Raintung, Jeane S.M.; Sompotan, Saartje; Porong, Jelie Viekson (Jurnal Agroekoteknologi Terapan (JAT), 2026)
Cauliflower (Brassica oleracea var. botrytis) production in tropical highlands often depends on high mineral fertilizer inputs, yet integrated nutrient management using locally available organic biostimulants may improve growth and yield while supporting soil quality. This study evaluated the effects of moringa (Moringa oleifera) leaf liquid organic fertilizer (POC) concentration and NPK compound fertilizer dose on cauliflower grown in Kakaskasen, Tomohon City, North Sulawesi, Indonesia (May–October 2025). A 3 × 3 factorial experiment was arranged in a randomized block design with three replications (27 experimental units). POC concentrations were 0, 100, and 200 mL L⁻¹, and NPK doses were 0, 100, and 200 kg ha⁻¹; chicken manure (10 t ha⁻¹ equivalent) was applied as a basal input. Plant height, leaf number, and curd weight were assessed at harvest (~70 days after transplanting) and analyzed by ANOVA followed by LSD (5%). No interaction between POC concentration and NPK dose was detected for the reported variables. Increasing POC significantly improved plant height and leaf number, with 200 mL L⁻¹ producing the tallest plants (40.00 cm) and the highest leaf number (16.11 leaves plant⁻¹). Curd weight increased markedly with POC from 112.47 g (0 mL L⁻¹) to 192.93 g (200 mL L⁻¹). NPK significantly increased plant height and curd weight, with the highest curd weight at 200 kg ha⁻¹ (174.77 g), while the NPK effect on leaf number was not significant. Overall, 200 mL L⁻¹ moringa-leaf POC combined with adequate NPK supply is recommended for further field-scale validation under Tomohon conditions. Keywords: Brassica oleracea; integrated nutrient management; liquid organic fertilizer; Moringa oleifera; NPK fertilizer